Foreign Experience and Use in Achieving Effective Use of Investments - Esanboevich, Isakov Ahmadali (Miasto Przyszłości, 2023)
Formation of an effective strategy of competitiveness of the enterprise. A country's national competitiveness and investment are closely and directly related: the more competitive a country is, the more it attracts direct investment.